La vie, la mort et la résurrection des objets archéologiques - Anne-Lise Guigues; Zahra Hashemi (Les Cahiers de l'École du Louvre)
The circulation of archaeological objects on the art market often results in a change in their status. The Luristan bronzes provide an opportunity to reflect on the way in which the biography of objects can be written in the case of archaeological artefacts, as well as on the various definitions of the life of an object, from its manufacture to its burial, then from its rediscovery to its exhibition. Antiquities from Luristan, unknown when they arrived on the art market in the early twentieth century, were first and foremost “collectors’ items” – dealers played a part in ascertaining their aesthetic and commercial value. The region where antiquities originated sometimes replaced the typology of object when it was described or sold. But archaeological research also gave these pieces a new identity, and they become “archaeological objects” once again. The Luristan bronzes illustrate the complexity of writing history in relation to new archaeological interpretations.